Formulation and Antibacterial Activity Evaluation of a Mouthwash Containing a Combination of Ethanolic Extracts of Basil Leaves (Ocimum sanctum L.) and Mint Leaves (Mentha piperita L.) against Streptococcus mutans - Nur Ulina M. Br. Turnip; Sunariati; Rosminar Hasibuan (Jurnal FARMASIMED (JFM), 2026)
Background: Dental caries was a tooth decay characterized by the progressive destruction of enamel and dentin caused by the metabolic activity of Streptococcus mutans. The prevention of dental caries could be achieved by using mouthwash. However, many commercial mouthwashes contained alcohol, which might cause side effects with long-term use. Therefore, a natural-based mouthwash formulation using basil leaves (Ocimum sanctum L.) and mint leaves (Mentha piperita L.) was needed, as both contained secondary metabolites with potential antibacterial activity. Objective: This study aimed to determine whether the combination of basil leaf extract and mint leaf extract could be formulated as a mouthwash and to evaluate its antibacterial activity against Streptococcus mutans. Methods: This study used an experimental design. Basil and mint leaves were extracted by maceration using 70% ethanol. The extracts were formulated into mouthwash preparations with concentrations of 20%:0% (F1), 0%:20% (F2), and 20%:20% (F3). The formulations were evaluated through pH, stability, and clarity tests. Antibacterial activity was assessed using the disc diffusion method. Results: The results showed that the combination of basil and mint leaf extracts met the requirements for pH, stability, and clarity tests. The antibacterial activity test showed inhibition zone diameters of 14.9 mm (moderate), 15.8 mm (strong), and 16.35 mm (strong) for F1, F2, and F3, respectively. The positive control showed an inhibition zone of 25.2 mm (very strong), while the negative control showed no inhibition zone. Conclusion: The combination of basil and mint leaf extracts could be formulated as a mouthwash, met the required evaluation parameters, and exhibited antibacterial activity against Streptococcus mutans.